Analisis Motor Brushless Direct Current Aksial Fluks 3 Fasa Menggunakan Magenet Permanen Neodymium Sebagai Prime Mover Generator - Sari, Mayang Karlia; Hadi, Widyono; Cahyadi, Widya (Majalah Ilmiah Teknologi Elektro; Vol 19 No 2 (2020): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2020.v19i02.P11, 2020)
The increase in the use of conventional motor causes an increase in the use of petroleum that cannot be renewed. To overcome it the use of conventional motor changes to electric motor. Electric motor that are often used is brush motor, but it has brush-loss. Electric motor created to overcome the weakness of brush motor. Electric motor that are designed has specification ie 6 slot and use 4 dan 8 magnet in rotor. The coil in every slot is 450 made by email wire with 0,3 mm diameter. This research is doing by measurement and calculation. Measurement is included measure magnetic field, motor voltage, frekuensi and rotational speed. Calculation is included power, torque, frekuensi and rotational speed. Motor testing is using 4 and 8 magnet in no load condition and with load condition. The first test on a 24 Volt supply voltage when using 4 magnets in no-load condition result a torque value of 1.09x10-3 Nm and a speed of 2794 RPM, when in load condition motor result torque value of 2,25x10 -3 and rotational speed of 1171 RPM. The second test on a 24 volt supply voltage when using 8 magnet in no-load condition motor result torque value of 3,38x10 -3 Nm and rotational speed of 1410 RPM, when in load condition motor result torque of 7,4x10-3 Nm and rotational speed 1410 RPM. Maximal value torque result in all test is 7,4x10 -3 and maximal rotational speed is 2794 RPM.